Understanding Worship as the Realization of Human Essence in Ibn ‘Arabi’s Philosophical Sufism - Faizi, Moh. (Journal of Islamic Thought and Philosophy, 2025)
This article explores the meaning of worship in the perspective of Ibn ʿArabi’s philosophical Sufism, focusing on its role as a means for realizing the essence of the human being. In Islamic tradition, worship is generally understood as a set of ritual activities that affirm a servant’s obedience to God. Ibn ʿArabi, however, offers a more profound and philosophical approach, in which worship is seen as an ontological process that enables the human being to recognize their deepest identity as a creature reflecting the Divine names and attributes. This study employs a literature-based method, analyzing Ibn ʿArabi’s major works alongside interpretations offered by Sufi scholars. The findings show that, according to Ibn ʿArabi, worship serves as a path to unveiling the existential reality of the human being and actualizing their spiritual perfection as the insān kāmil. Thus, worship is not merely an outward practice but also a medium through which human consciousness becomes aligned with the source of its being. This understanding offers a significant contribution to renewing perspectives on worship within the context of contemporary spirituality.